Plumbers and pipe fitters library : materials, tools, calculations - Oravetz, Jules Sr. (Indianapolis : Theodore Audel, 1967)
This book have been written to aid those who are active in these trade and to aid those who desire to become plumbers and pipe fitters
Includes index
oif 16/08/2019
Loans
Keywords: Pipe fitting; Plumbing; Water-supply; Building